On the role of classical and novel forms of vitamin D in melanoma progression and management. Issue 177 (March 2018) - Slominski, Andrzej T.; Brożyna, Anna A.; Skobowiat, Cezary; Zmijewski, Michal A.; Kim, Tae-Kang; Janjetovic, Zorica; Oak, Allen S.; Jozwicki, Wojciech; Jetten, Anton M.; Mason, Rebecca S.; Elmets, Craig; Li, We; et al.
Highlights: Active forms of vitamin D inhibit growth of melanomas in vitro and in vivo . Defects in vitamin D receptors and activating enzymes affect melanomagenesis and melanoma progression. Active forms of vitamin D warrant pre- and clinical testing against melanoma. Vitamin D can be used as an adjuvant factor in melanoma therapy. Abstract: Melanoma represents a significant clinical problem affecting a large segment of the population with a relatively high incidence and mortality rate. Ultraviolet radiation (UVR) is an important etiological factor in malignant transformation of melanocytes and melanoma development. UVB, while being a full carcinogen in melanomagenesis, is also necessary for the cutaneous production of vitamin D3 (D3). Calcitriol (1, 25(OH)2 D3) and novel CYP11A1-derived hydroxyderivatives of D3 show anti-melanoma activities and protective properties against damage induced by UVB. The former activities include inhibitory effects on proliferation, plating efficiency and anchorage-independent growth of cultured human and rodent melanomas in vitro, as well as the in vivo inhibition of tumor growth by 20(OH)D3 after injection of human melanoma cells into immunodeficient mice. The literature indicates that low levels of 25(OH)D3 are associated with more advanced melanomas and reduced patient survivals, while single nucleotide polymorphisms of the vitamin D receptor or the D3 binding protein gene affect development or progression of melanoma, or disease outcome. An inverse correlation of VDR and CYP27B1 expression with melanoma progression has been found, with low or undetectable levels of these proteins being associated with poor disease outcomes. Unexpectedly, increased expression of CYP24A1 was associated with better melanoma prognosis. In addition, decreased expression of retinoic acid orphan receptors α and γ, which can also bind vitamin D3 hydroxyderivatives, showed positive association with melanoma progression and shorter disease-free and overall survival. Thus, inadequate levels of biologically active forms of D3 and disturbances in expression of the target receptors, or D3 activating or inactivating enzymes, can affect melanomagenesis and disease progression. We therefore propose that inclusion of vitamin D into melanoma management should be beneficial for patients, at least as an adjuvant approach. The presence of multiple hydroxyderivatives of D3 in skin that show anti-melanoma activity in experimental models and which may act on alternative receptors, will be a future consideration when planning which forms of vitamin D to use for melanoma therapy.